2022
DOI: 10.1177/10812865221108373
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity contribution tensor for two non-conductive overlapping spheres having different radii

Abstract: We consider here the problem of a three-dimensional (3D) body subjected to an arbitrarily oriented and remotely applied stationary heat flux. The body includes a non-conductive inhomogeneity (or pore) having the shape of two intersecting spheres with different radii. Using toroidal coordinates, the steady-state temperature field and the heat flux have been expressed in terms of Mehler–Fock transforms. Then, by imposing Neumann BCs at the surface of the spheres, a system of two Fredholm integral equations is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Let x = (x, y, z) denote the position vector on the sphere surface, then (2.1) yields: where is the volume of the two tangent spheres. Note that for ρ = 1 then R zz = −1.3523/k and thus the result obtained by Lanzoni et al (2020) for two equal touching spheres is fully recovered. Note also that, keeping fixed the thermal conductivity k, one has R zz (ρ) = R zz (1/ρ) and that k R zz → 3/2 as ρ → 0, + ∞, as predicted for a single sphere (Kachanov & Sevostianov, 2018).…”
Section: Axial Component Of the Resistivity Contribution Tensorsupporting
confidence: 52%
See 3 more Smart Citations
“…Let x = (x, y, z) denote the position vector on the sphere surface, then (2.1) yields: where is the volume of the two tangent spheres. Note that for ρ = 1 then R zz = −1.3523/k and thus the result obtained by Lanzoni et al (2020) for two equal touching spheres is fully recovered. Note also that, keeping fixed the thermal conductivity k, one has R zz (ρ) = R zz (1/ρ) and that k R zz → 3/2 as ρ → 0, + ∞, as predicted for a single sphere (Kachanov & Sevostianov, 2018).…”
Section: Axial Component Of the Resistivity Contribution Tensorsupporting
confidence: 52%
“…Kushch and Sevostianov (2014) showed that shape, orientation, and spatial arrangement of the inhomogeneities in particulate composites may produce macroscopic anisotropy of the overall conductivity, whereas volume content of inhomogeneities yields the change in the anisotropy extent. Radi and Sevostianov (2016) and Lanzoni et al (2018Lanzoni et al ( , 2020Lanzoni et al ( , 2022 worked out the components of the resistivity contribution tensor for insulating inhomogeneities having the shape of a torus as well as that two overlapping cylinders or spheres of arbitrary size. The analytical results were then compared with the predictions provided by equivalent spheroids, finding a reasonable agreement within a definite range of variation of the geometrical parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations